Resource-based economy – determinants of economic growth and sustainable development in Saudi Arabia - Sandra Šokčević; Andreja Rudančić; Matea Pandžić (Ekonomski Vjesnik, 2023)
Purpose: This paper examines the determinants of long-term economic growth and sustainable development of the Kingdom of Saudi Arabia as a chosen one-resource economy that relies on massive oil production. Methodology is based on the econometric methods of multiple regression analysis and the multicollinearity test for the period from 2010 to 2020. The research was conducted on the basis of a model of 13 variables, where the dependent variable is the annual rate of GDP, and the independent variables are inflation, budget deficit, oil exports, imports, unemployment rate, foreign direct investment, labour productivity, public debt, labour force, GDP per capita, HDI index, total rent of natural resources and adjusted net savings. Results indicate a strong connection between gross domestic product and the selected variables and the existence of factors that are of strategic importance for the growth of the Saudi economy, but on the other hand, the negative effects of certain factors on sustainable development. Conclusion: Based on the results, it is suggested that investment in human capital is an urgent step to achieve long-term sustainability and reduce reliance on natural resource operations in the future.